The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1093/infdis/170.4.986
|View full text |Cite
|
Sign up to set email alerts
|

National Surveillance For Respiratory Syncytial Virus, United States, 1985-1990

Abstract: Respiratory syncytial virus (RSV) causes pneumonia and bronchiolitis in infants and young children and serious disease in the elderly and persons with compromised immune systems. To determine the temporal and geographic patterns of RSV outbreaks in the United States, monthly reports from 74 laboratories were analyzed for July 1985 through June 1990. RSV outbreaks were identified in 197 (93%) of the 211 laboratory years analyzed, with widespread activity beginning each fall, peaking in winter, and returning to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
64
1
6

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 13 publications
5
64
1
6
Order By: Relevance
“…[10][11][12][13] Recommendations for the management of RSV infections in cancer patients include strict infection control measures, delay in the therapy for the underlying disease, and treatment with aerosolized ribavirin plus high-dose intravenous immunoglobulin (IVIG). [3][4][5][6][7][8][9]14 These strategies are associated with huge costs, toxicity, disruption of patient care activities, and delay in treating the underlying cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Recommendations for the management of RSV infections in cancer patients include strict infection control measures, delay in the therapy for the underlying disease, and treatment with aerosolized ribavirin plus high-dose intravenous immunoglobulin (IVIG). [3][4][5][6][7][8][9]14 These strategies are associated with huge costs, toxicity, disruption of patient care activities, and delay in treating the underlying cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Several prospective studies have also indicated that lower respiratory tract RSV infections in hospitalised [8] and nonhospitalised [9] infants, result in an excess of recurrent lower respiratory tract symptoms in subsequent years. These symptoms decline progressively over the first decade of life but the cause for this excess morbidity remains unclear [10].There has been much speculation regarding the nature of the host/virus interaction [3,11] and more than 30 yrs ago it was proposed that RSV bronchiolitis is a consequence of a specific immunopathology.Despite much research to demonstrate this, no distinct immunopathological process has been identified. The current authors have shown that neutrophils are the predominant inflammatory cell in the upper and lower airway in RSV infections in infants, accounting for y80% of cells recovered from the tracts [12].…”
mentioning
confidence: 99%
“…Respiratory syncytial virus (RSV) is responsible for annual epidemics of respiratory disease affecting the whole population [1][2][3] and particularly infants of whom the majority are infected during their first winter [1,4,5]. Of these, 20-30% develop lower respiratory tract symptoms and 0.5-2% are hospitalised with RSV bronchiolitis [1,2,4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, HRSV is the most common cause of bronchiolitis-associated hospitalizations in infants (18,25). HRSV is also a significant cause of excess morbidity and mortality in adult patients with compromised immune status and chronic inflammatory lung disease and in the elderly (10,12,13,37).…”
mentioning
confidence: 99%